Pang, King Wah - (:unkn) unknown (My University, 2026)
Anthony PANG is Associate Professor in the Department of Logistics and Maritime Studies at The Hong Kong Polytechnic University. He received his Doctoral degree from The Hong Kong University of Science and Technology. His research interest lies in logistics and supply chain management, optimization and metaheuristics, containership and terminal operations. He has published more than ten research papers in international conferences and journals, including IIE Transactions, Computer-Aided Design, International Journal of Production Economics and International Journal in Shipping and Transport Logistics.